Prototipe Manajemen Beban Otomatis Pada Sistem Tenaga Listrik Tegangan Rendah 1 Phasa - Setyawan, Herry (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2019)
The use of electricity now has become a basic requirement for modern society, not only in industry and offices, but also in housing. The problem with the distribution of electricity is that the power consumed must not exceed the current limiting installed because the increase in load causes the current to rise. Problems will arise if the continuity of electricity supply from PLN goes out due to overload, which will result in the activity stalled. The outage of electricity supply from PLN due to overload (over load) causes the users of electrical equipment to lose time and costs. The effects of sudden outages caused by overloading can damage electronic equipment. The system is made using AT89S51 microcontroller. The test results show that testing at each point shows that there is a linear relationship between the current measured by the output at each point. If there is a load group that has been extinguished but the ampere meter display still shows 2.00, the other load groups will be extinguished in a 60 second delay, until the ampere meter display shows a number below 2.00.Data SDYhttps://materassomemory.org/https://visualresearchnetwork.org/https://brazoriafumc.org/https://atmamayor.com/https://viralblasts.com/Bloom ScapeRokokbetRokokbetScatter HitamRokokbethttps://press.umam.edu.my/Rokokbethttps://theusajournals.com/RokokbetShiowlaRokokbetRokokbetRokokbetRokokbetRokokbetShiowla